Aplikasi Multimedia Interaktif Tumbuh Kembang Anak Berbasis Web - Wahyuddin Wahyuddin; Muh Yusri; A. Irmayani Pawelloi (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Child development is an important process that must be monitored so that it can run optimally. At In the early stages of life, monitoring can be done by parents, who are the closest people to the child. Unfortunately, not all parents have enough time to attend health education sessions. This study aims to make it easier to monitor children's growth and health. Methods The research method used is descriptive research, namely activities carried out by collecting data directly from the object of research through interviews, surveys, and interviews. Object of research through interviews, observation, and document collection. The result of the research shows that the application can be used to monitor the nutritional status of children, calculate weight and height, and see the location of the nearest health center, which is useful for monitoring the nutritional status of children, location of the nearest health center, which is useful for monitoring.